2019
DOI: 10.1099/ijsem.0.004702
|View full text |Cite
|
Sign up to set email alerts
|

Megasphaera lornae sp. nov., Megasphaera hutchinsoni sp. nov., and Megasphaera vaginalis sp. nov.: novel bacteria isolated from the female genital tract

Abstract: Six strictly anaerobic Gram-negative bacteria representing three novel species were isolated from the female reproductive tract. The proposed type strains for each species were designated UPII 199-6T, KA00182T and BV3C16-1T. Phylogenetic analyses based on 16S rRNA gene sequencing indicated that the bacterial isolates were members of the genus Megasphaera . UPII 199-6T and KA00182T had 16S rRNA gene sequence identities of 99.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 70 publications
(156 reference statements)
0
21
0
Order By: Relevance
“…Taxa identified as contributing to these differences were Coriobacteriaceae OTU27, Megasphaera OTU71_type1 (recently renamed Megasphaera lornae sp. nov) (28), Saccharibacteria TM7 OTUH1, Prevotellaceae OTU61, and Mobiluncus mulieris (Figure 3). The full heat map analysis is noted in Supporting Information Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Taxa identified as contributing to these differences were Coriobacteriaceae OTU27, Megasphaera OTU71_type1 (recently renamed Megasphaera lornae sp. nov) (28), Saccharibacteria TM7 OTUH1, Prevotellaceae OTU61, and Mobiluncus mulieris (Figure 3). The full heat map analysis is noted in Supporting Information Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an increase in Succinivibrio and Megasphaera have been described in infected patients under antiretroviral therapy [ 40 ]. In addition, the Megasphaera genus has been found in high proportion in healthy vaginal microbiota, especially in the genital tract [ 41 ]. It is important to note that most HESN in this study were female, and their HIV-infected partners were on ART at sampling, which could explain the enrichment of these genera in HESN.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the production of favorable short-chain fatty acids (SCFA) by some bacteria has anti-inflammatory, antitumorigenic, and antimicrobial effects, maintaining gut integrity and immune homeostasis [ 42 ]. Interestingly, genera enriched in HESN such as Succinivibrio , Megasphaera , Butyrivibrio , and Victivallis are known SCFA-producers [ 41 44 ], suggesting a larger SFCA pool in HESN than HIV+ subjects. However, the relevance of these genera in HESNs remains to be fully described.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our repeated attempts to recover the isolates from frozen stocks were not successful, and we were thus unable to perform biochemical assays. Since our initial submission, Srinivasan et al confirmed that none of the vaginal Megasphaera, including MP2, were able to use glucose as a carbon source [ 83 ].…”
Section: Resultsmentioning
confidence: 99%